"Designerly" Ways of Reading: Insights From Reader Response in Drama for Enriching the "A" in Language Arts (LEARNing Landscapes, 2016)
In this interpretive case study of reader response in drama, a drama troupe is the context for illuminating how young actors read in "designerly" ways; that is, how their reading processes facilitated constructive, solution-focused thinking in their development of characterizations. By examining the nature of reader response in the drama troupe, I hope to help educators understand how design thinking occurred as an aesthetic reading practice and consider ways in which design thinking can be cultivated in the language arts classroom. I argue that design thinking inspires the young to engage the imagination, practice teamwork, and take risks as they work to make their visions real. Perhaps most importantly, I contend that design thinking can help prepare the young for facing complex and highly ambiguous problems characteristic of 21st century participatory cultures.
Keywords: interpretive; case study; reading; reader response; drama; design thinking; art